2008
DOI: 10.1203/pdr.0b013e318175dd2d
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage MMP-9 and TIMP-1 in Preschool Wheezers and Their Relationship to Persistent Wheeze

Abstract: Atopic preschool children are more likely to develop persistent wheezing, which could be a consequence of early airway remodeling. Protease-antiprotease balance between MMP-9 and its cognate inhibitor TIMP-1 may be involved in this process. Our hypothesis was that atopic wheezing preschool children would have an imbalance of MMP-9 to TIMP-1 in bronchoalveolar lavage (BAL). BAL from 52 preschool wheezers was compared with 14 controls without wheeze. A subgroup completed an International Study of Asthma and Alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…The extracellular activity of MMPs is regulated by TIMPs, which are produced by the same cell types that produce MMPs, and TIMP-1 has been implicated as a natural inhibitor of both MMP-7 and 9 (27)(28). It has been shown that MMP7 and 9 is upregulated in chronic rhinosinusitis with or without polyps (29) and the ratio of MMP-9/TIMP-1 is increased in asthmatics (30)(31). Recently it has been demonstrated that only MMP-9 but not MMP-2 or TIMP-1 mRNA expression is increased in nasal mucosa of severe perennial allergic rhinitis compared to mild rhinitics and healthy controls (32).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular activity of MMPs is regulated by TIMPs, which are produced by the same cell types that produce MMPs, and TIMP-1 has been implicated as a natural inhibitor of both MMP-7 and 9 (27)(28). It has been shown that MMP7 and 9 is upregulated in chronic rhinosinusitis with or without polyps (29) and the ratio of MMP-9/TIMP-1 is increased in asthmatics (30)(31). Recently it has been demonstrated that only MMP-9 but not MMP-2 or TIMP-1 mRNA expression is increased in nasal mucosa of severe perennial allergic rhinitis compared to mild rhinitics and healthy controls (32).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 levels have been demonstrated to increase BAL in preschool wheezers when compared to healthy controls; however, the difference disappeared when the wheezers were divided into those with atopic and nonatopic asthma [47]. Similarly, MMP-9 levels were demonstrated to be higher in the induced sputum of patients with atopic asthma when compared to the patients with nonatopic asthma, but with no statistical significance [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increased expression of several members of the chemokine and cytokine family and genes encoding additional complement components, we particularly observed increased expression of genes encoding proteins, such as Saa3, Timp1, and serine peptidase inhibitor, clade A, member 3N (Serpina3n). Although Timp1 was reported to play a role in extracellular matrix remodeling, and its role in the development of allergic asthma is well described (30,31), the functional role of Serpina3n has not been established. In humans, SERPIN3A, commonly known as antichymotrypsin, is produced by a variety of cell types, including hepatocytes and bronchial epithelial cells during acute inflammatory responses, and studies showed that serum levels of two other serpin family members, SERPINB3 and SERPINB4, are elevated in patients with asthma (32,33).…”
Section: Discussionmentioning
confidence: 99%